2016
DOI: 10.21767/2577-0578.10027
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and Anxiety and Depression Disorders: Prospective Cohort Study in Primary Care

Abstract: Introduction: Anxiety and depression are underdiagnosed in Chronic Obstructive Pulmonary Disease (COPD) patients. Few studies have tried to identify their association with hospitalization (severe exacerbation). The objective of this study was to determine whether the anxiety/depression was associated with severe exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Andrenas et al ascertained that most of the patients evaluated their stressful situation as a threat, and challenging issue which inversely affects their coping skills with distressful disorders [21]. They also believed that such worrying conditions have a harmful effect on patients' mental health and their quality of life [22][23][24]. Literature also revealed that deterioration in the immune system of patients with anxiety and depression is more likely which eventually weakens their resistance toward pathogens [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Andrenas et al ascertained that most of the patients evaluated their stressful situation as a threat, and challenging issue which inversely affects their coping skills with distressful disorders [21]. They also believed that such worrying conditions have a harmful effect on patients' mental health and their quality of life [22][23][24]. Literature also revealed that deterioration in the immune system of patients with anxiety and depression is more likely which eventually weakens their resistance toward pathogens [25][26][27].…”
Section: Discussionmentioning
confidence: 99%